2007
DOI: 10.1038/sj.ejcn.1602821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate alcohol consumption on adipokines and insulin sensitivity in lean and overweight men: a diet intervention study

Abstract: Objective: Moderate alcohol consumption is associated with a decreased risk of type II diabetes. This study investigates the effect of moderate alcohol consumption on adipokines and insulin sensitivity. Subjects: Twenty healthy, lean (body mass index (BMI) 18.5-25 kg/m 2 ; n ¼ 11) or overweight (BMI427 kg/m 2 ; n ¼ 9) men (18-25 years). Methods: Three cans of beer (40 g alcohol) or alcohol-free beer daily during 3 weeks. Results: Adiponectin and ghrelin concentrations increased (Po0.01) by 11 and 8%, while acy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
76
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 39 publications
(56 reference statements)
6
76
0
Order By: Relevance
“…Epidemiological studies on the link between alcohol consumption and BW are conflicting; some studies show a positive relationship, in which increased alcohol intake is associated with higher BW, 10,24,25 whereas others show a negative relationship, in which increased alcohol intake is associated with lower BW; 26,27 still others show no relationship. 28 The lack of a clear trend in these studies is likely because of the large number of confounders associated with human studies.…”
Section: Discussionmentioning
confidence: 93%
“…Epidemiological studies on the link between alcohol consumption and BW are conflicting; some studies show a positive relationship, in which increased alcohol intake is associated with higher BW, 10,24,25 whereas others show a negative relationship, in which increased alcohol intake is associated with lower BW; 26,27 still others show no relationship. 28 The lack of a clear trend in these studies is likely because of the large number of confounders associated with human studies.…”
Section: Discussionmentioning
confidence: 93%
“…For example, alcohol consumption has been shown to raise high-density lipoprotein cholesterol 21 ; improve insulin sensitivity and lower the risk of diabetes mellitus 22,23 ; lower plasma levels of inflammatory markers 24 ; and raise plasma levels of adiponectin 25,26 . In experimental studies, adiponectin has been shown to attenuate cardiac hypertrophy in response to pressure overload in adiponectin knockout mice 27 .…”
Section: Discussionmentioning
confidence: 99%
“…This risk reduction could be explained by improved insulin sensitivity with moderate alcohol consumption. However, this relationship has only been demonstrated by two randomized controlled trials amongst postmenopausal women [2,3]; other studies amongst men were not able to detect such an increase in insulin sensitivity [4][5][6][7][8]. A metaanalysis of observational studies quantified the association between alcohol consumption and risk of type 2 diabetes [1]: compared with nondrinkers, a significantly reduced risk of 13% [95% confidence interval (CI): 0-24] at 22 g day )1 was observed amongst men, whilst this risk reduction reached about 40% (95% CI: 31-48) at 24 g day )1 amongst women.…”
Section: Introductionmentioning
confidence: 99%